MASTER'S DEGREE IN INTERNATIONAL RELATIONS AND WORLD POLITICS (Spectrum Journal of Innovation, Reforms and Development, 2025)
Ensuring peace and stability on a global scale has always been a matter of great importance. The role of religion in this process is interpreted in different ways. In some cases, religion is seen as a source of conflict, while in others, it serves as a tool for strengthening peace. This article analyzes the role of religion in maintaining peace and stability, explores international experiences, and examines the place of religious values in dialogue and diplomacy.